Physical Restraint, Seclusion, and Time-Out Rooms in Canadian Schools: Analysis of a Policy Patchwork - Bartlett, Nadine Alice; Floyd Ellis, Taylor (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
The intended purpose of physical restraint, seclusion, and time-out rooms in schools is to intervene in a crisis when the behaviour of a student poses an immediate or imminent, and significant threat to physical safety. While the use of physical restraint, seclusion, and time-out rooms is intended to provide protection from immediate physical harm, there is increasing concern that these practices are being used more broadly and that individuals with disabilities are disproportionately subjected to their use. In spite of the importance of this issue, there is a dearth of research analyzing the policy landscape of physical restraint, seclusion, and time-out rooms in Canadian schools. In order to explore this issue, a comparative analysis of publicly available provincial and territorial education documents was conducted. The analysis revealed that in many Canadian provinces and territories, policies and accountability structures on the use of physical restraint, seclusion, and time-out rooms in schools are inconsistent or non-existent. Further, the terminology used to describe seclusion is variable and often conflated with time out, and the conditions under which such practices may be used in some instances are subjective, which may contribute to a broad interpretation of what is deemed acceptable practices in schools. This analysis draws attention to the need for the development of clearly articulated provincial and territorial standards for the use of physical restraint, seclusion, and time out, as well as the need for regulatory and enforcement mechanisms at the school, division, and ministry levels in order to ensure the emotional and physical well-being of all.